Educational blog and the teaching of folk dances in physical education classes: Approaches from the São Paulo state curriculum - Diniz, Irlla Karla dos Santos; Darido, Suraya Cristina [UNESP] (Universidade Federal do Rio Grande do Sul, 2015)
The aim of this study was to develop and evaluate supplementary teaching . materials to the curriculum of Physical Education of the State of São Paulo in the form of educational blog of folk dances. A qualitative survey was conducted in three steps: documentary analysis of curriculum in relation to dance, blog production, and evaluation by teachers. The blog was indicated as a continuing training tool enabling quick access and gathering various media in the same virtual space. However, limitations were identified in the use of this tool for the organization of dance knowledge, the school structure and the conditions of teaching.
Blog educativo y la enseñanza de danzas folclóricas en educación física: Enfoques del currículo estado de São Paulo
Blog educacional e o ensino das danças folclóricas nas aulas de educação física: Aproximações a partir do currículo do estado de São Paulo
Keywords: Blog; Curriculum; Dance; Physical education